2014
DOI: 10.1155/2014/527030
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Spontaneous Clearance of Hepatitis C Virus in Chinese Population

Abstract: Hepatitis C virus (HCV) infections spontaneously clear in approximately 15–45% of infected individuals. Factors which influence spontaneous HCV clearance remain to be identified. The purpose of the present study was to identify variables associated with spontaneous HCV clearance in a referred population of Chinese patients. The prevalence of host, viral, and environmental factors known to influence the outcome of HCV infections was compared in 92 HCV spontaneous clearance subjects and 318 HCV persistent infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 37 publications
3
16
1
Order By: Relevance
“…It is likely that genotype 1 clears faster and thus remains untypable contributing highly to the “unknown” category. Our analysis also found females to have higher likelihood of spontaneous clearance of HCV compared to males, which was maintained across the sensitivity analyses among seroconverters, and is consistent with the findings from other epidemiological studies . This disparity in spontaneous clearance of HCV has been suggested to be linked with sex hormones, particularly oestrogen .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…It is likely that genotype 1 clears faster and thus remains untypable contributing highly to the “unknown” category. Our analysis also found females to have higher likelihood of spontaneous clearance of HCV compared to males, which was maintained across the sensitivity analyses among seroconverters, and is consistent with the findings from other epidemiological studies . This disparity in spontaneous clearance of HCV has been suggested to be linked with sex hormones, particularly oestrogen .…”
Section: Discussionsupporting
confidence: 90%
“…Coinfection with HBV was associated with a higher likelihood of spontaneous clearance of HCV which is consistent with previous findings in specific high-risk cohorts. 11,17 The study on PWIDs by Grebely et al 3 also reported similar trend but HBV did not reach statistical significance, which may be due to very small number of cases with viral clearance (n=9). Previous research suggested that HBV superinfection may suppress the pre-existing HCV infections.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…HCV infections spontaneously clear in approximately 15-45% of infected individuals [22,23]. Currently, there is a strong association between the rate of spontaneous clearance of HCV and IFN-λ polymorphisms [24].…”
Section: Interleukin-28b Polymorphism Is a Pharmacogenetic Predictor mentioning
confidence: 99%